Lisbon-s airbnb market and gentrification - current developments through the pandemic the implications for public policy - Heinermann, Louis (2023)
Lisbon’s seemingly unstoppable growth of Airbnbs and the coherently gentrification, have been interrupted during Covid-19. As tourist flows are returning to the city, this paper focuses on the changes in the short-term rental market, addresses the current impact of gentrification/touristification in Lisbon’s Civil Parishes, and identifies which aspects drive resilience and significant price increases for short-term rentals. Moreover, it shows trends in the market and gives implications for legislators